The “double-edged” role of progesterone in periodontitis among perimenopausal women undergoing or not undergoing scaling and root planing - Yan, Shengjie; Man, Ying; Lu, Jun; Cui, Liyun; Niu, Feifei; Qin, Jianyong (Frontiers in Endocrinology, 2023)
Abstract Objective: Progesterone (PG) is an important sex steroid hormone commonly administered to protect the endometrium in perimenopausal women. The present study aimed to explore differential responses of periodontitis to PG in perimenopausal women who did or did not undergo scaling and root planing (SRP). Methods: A total of 129 perimenopausal women with mild-to-moderate periodontitis were enrolled and underwent treatment as follows: SRP (n = 35); SRP + PG (n = 34); PG (n = 31); and no treatment (s) (n = 29). Pocket probing depth (PPD), clinical attachment level (CAL), sulcus bleeding index (SBI), and bleeding on probing (BOP) were measured using periodontal probes. Three inflammatory markers, including C-reactive protein (CRP), interleukin (IL)-6, and tumor necrosis factor-alpha (TNF-α) in gingival crevicular fluid (GCF) were measured using ELISA techniques. Results: PPD, CAL, SBI, BOP, and levels of inflammatory factors in GCF were all significantly decreased in perimenopausal women with periodontitis after SRP. In patients who did not undergo SRP, 6 months of PG treatment significantly elevated PPD, SBI, BOP, and GCF levels of CRP, IL-6, and TNF-α. In contrast, PG exhibited inhibitory effects on periodontal inflammation in patients who underwent SRP, evidenced by significantly decreased BOP and IL-6, and slightly decreased SBI, CRP, and TNF-α. PG-induced changes dissipated 6 months after withdrawal of PG (at 12 months). Conclusions: Among perimenopausal women with periodontitis, PG enhanced periodontal inflammation in the absence of SRP but inhibited periodontal inflammation in those who underwent SRP.